1966
DOI: 10.1172/jci105496
|View full text |Cite
|
Sign up to set email alerts
|

Studies on infant diarrhea. II. Absorption of glucose and net fluxes of water and sodium chloride in a segment of the jejunum.

Abstract: Increased stool losses of water, solute, and organic acids after the ingestion of milk during acute diarrhea of infancy have been related to impaired absorption of carbohydrate (1). We have observed that the osmolality of diarrheal stool water is usually high during periods of milk intake. Furthermore, we have demonstrated that carbohydrate comprises most of the solute content of the stool water and that there exists a reciprocal relationship between the concentration of this compound and that of Cl-, Na+, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…The fluid loss in other types of diarrheal disorders may be produced by secretory processes similar to those in cholera. In this respect, the study of cholera, both in man and the animal models, may help in understanding the diarrhea associated with Escherichia coli (30), staphylococci (31), or other toxin-producing microorganisms. …”
Section: Discussionmentioning
confidence: 99%
“…The fluid loss in other types of diarrheal disorders may be produced by secretory processes similar to those in cholera. In this respect, the study of cholera, both in man and the animal models, may help in understanding the diarrhea associated with Escherichia coli (30), staphylococci (31), or other toxin-producing microorganisms. …”
Section: Discussionmentioning
confidence: 99%
“…Torres-Pinedo, Rivera, Fernandez, and Maldonado (25), using a similar perfusion technique demonstrated that glucose absorption was impaired in the proximal jejunum of infants with enteropathogenic E. coli diarrhea. In the presence of a perfused glucose load the defect in glucose absorption resulted in a reduction in net absorption of fluid and electrolytes from the small intestine and an accumulation of osmotically active products in the lumen which induced fluid secretion.…”
Section: Intestinal Biopsiesmentioning
confidence: 90%
“…This reinforced Ingelfinger’s emphasis on the conjoint need for both sodium and glucose to facilitate absorption. John Banwell told me that my studies on malnutrition and gastroenteritis, together with those of Torres-Pinedo [9] in Puerto Rico (whom I visited during my studies), had justified him and his colleagues in Dhaka, Bangladesh to advocate the use of glucose/saline for children in the community with gastroenteritis as well as for their patients with cholera [10]. This has already saved 93% of deaths in clinical settings and probably many further millions in the community [11].…”
Section: Stimulating the Use Of Sugar/saline Treatment For Childhood mentioning
confidence: 99%